The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1111/j.1528-1157.1986.tb03496.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Acetazolamide Administration in DBA and C57 Mice: Effects of Age

Abstract: The clinical utility of the carbonic anhydrase (CA) inhibitor acetazolamide (ACTZ) is limited because of rapid development of tolerance to its effects. Tolerance is thought to develop as a result of glial cell proliferation and/or increased CA synthesis. DBA mice, susceptible to audiogenic seizures (AGSs) in an age-dependent manner, have increased CA activity as compared with C57 (non-audiogenic seizure susceptible) mice at 21 and 110 days of age. The present work utilized ACTZ to help determine the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 5 publications
(9 reference statements)
1
11
1
Order By: Relevance
“…D2 mice are exquisitely sensitive to soundinduced (audiogenic) seizures until the age of -3 weeks (Hall, 1947). Although D2 mice acquire resistance to audiogenic seizures with maturity, previous work has shown that they remain hyperexcit-able to electrical stimulation throughout adult life (Engstrom et al, 1986). Results of our study confirm that mature D2 mice are more vulnerable than mature B6 mice to induction of behavioral seizures after systemic injection of KA.…”
Section: Discussionsupporting
confidence: 75%
“…D2 mice are exquisitely sensitive to soundinduced (audiogenic) seizures until the age of -3 weeks (Hall, 1947). Although D2 mice acquire resistance to audiogenic seizures with maturity, previous work has shown that they remain hyperexcit-able to electrical stimulation throughout adult life (Engstrom et al, 1986). Results of our study confirm that mature D2 mice are more vulnerable than mature B6 mice to induction of behavioral seizures after systemic injection of KA.…”
Section: Discussionsupporting
confidence: 75%
“…In CS7 mice, the maximum amount of enzyme per cell at each dose was obtained 24 h after beginning treatment and no further increases were observed with time (Fig. Nevertheless, the persistent increases in CA in DBA mice may explain why they do not become tolerant to the protective effects of acetazolamide on MES (Engstrom et al, 1986). In contrast, the amount of enzymes per cell in DBA mice continued to increase with time and dose up to S days after beginning acetazolamide treatment (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…Tolerance to protection from MES develops in C57, but not in DBA mice (Engstrom et al, 1986). The elevated quantity of CA in DBA mice, thus, may represent the effects of a functional inhibition of the enzyme.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations